Legal framework in Panama for the handling of containers and packaging - Avilés, Shajany; Figueroa, Ornelis; Morales, Loannik; Samudio, Lidia; Bernal, katherine; González, Génesis; Rosas, Edgar; Sierra, Hermes Mauricio (Revista Semilla Científica, 2020)
With this research, the students of the subject Packaging and Brand learned more about the regulations in Panama for the commercialization of a product in the national territory. Through data collection it was proved that the hypothesis where the consumer is an important player in marketing who does not know his role and the legal framework that the company must fulfill. The main conclusion of everything investigated, we consider that the companies that set trends have good practices, these good practices include the regulations or laws established in the handling of the packaging and its packaging; that is to say that in their process they establish the norms established by the regulatory entities. To do this, they place their brand as a reference and market leader.